Judicial Control of Administrative Discretion by The Administrative Court : A Study on Justifiable Grounds for Mitigating Disciplinary Penalties in Cases of Serious Misconduct by Subdistrict Officials - Atchanakin, Tossaporn; Raksuwan, Arnuphab (Journal of Law and Political Affairs, 2025)
This independent legal research aims to study the concepts, theories, and relevant laws concerning discipline, disciplinary penalties, mitigating factors for disciplinary penalties of subdistrict administrative organization officers, the administrative discretion, fact-finding procedures of the Administrative Court regarding mitigating factors for disciplinary penalties, and judicial review of administrative discretion by the Administrative Court. The research serves as a source of information to highlight issues related to mitigating factors in cases where subdistrict administrative organization officers commit serious disciplinary offenses, the fact-finding procedures of the Administrative Court concerning mitigating factors for disciplinary penalties in such cases, as well as the judicial review of the discretion exercised by state officials in issuing orders to determine the level of disciplinary penalties. The study found that Clause 85 of the Announcement of the Central Committee on Subdistrict Administrative Organization Officers regarding General Standards on Discipline, Maintenance of Discipline, and Disciplinary Proceedings, B.E. 2558 (2015), does not specify which circumstances qualify as mitigating factors for disciplinary penalties. Consequently, disciplinary authorities lack a clear framework for exercising their discretion. Moreover, in adjudicating administrative cases related to discipline, the Administrative Court tends to review the exercise of discretion in cases where the superior authority did not grant a reduction of the penalty. However, if the petitioner asserts a claim based on mitigating factors, the court will examine whether the claimed circumstances indeed constitute valid mitigating factors. In contrast, the court generally refrains from reviewing cases where the superior authority has already granted a reduction of the penalty based on its determination that mitigating factors exist. This study provides the following recommendations: it is suggested that Clause 85, Paragraph 2 of the Announcement of the Central Committee on Subdistrict Administrative Organization Officers regarding General Standards on Discipline, Maintenance of Discipline, and Disciplinary Proceedings, B.E. 2558 (2015) should be amended to explicitly specify what constitutes mitigating factors for disciplinary penalties. Additionally, it is recommended that the Administrative Court, through the Office of the Administrative Court, should organize seminars to gather opinions from justices of the Supreme Administrative Court and the Administrative Courts of First Instance regarding the judicial review of discretion in determining disciplinary penalties in cases where mitigating factors exist.